2018
DOI: 10.1523/jneurosci.1214-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Dynamics of GABA and Glutamate Levels in the Occipital Cortex during Visual Processing

Abstract: Magnetic resonance spectroscopy (MRS) measures the two most common inhibitory and excitatory neurotransmitters, GABA and glutamate, in the human brain. However, the role of MRS-derived GABA and glutamate signals in relation to system-level neural signaling and behavior is not fully understood. In this study, we investigated levels of GABA and glutamate in the visual cortex of healthy human participants (both genders) in three functional states with increasing visual input. Compared with a baseline state of eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 37 publications
15
98
0
Order By: Relevance
“…By contrast, we found no relationships between the change in different metabolite concentrations. (Kurcyus et al, 2018). This work revealed that GABA+ concentrations were higher when participants had their eyes closed, compared to open in darkness, while Glx concentration was lower when participants eyes were closed, compared to when receiving visual stimulation.…”
Section: Low Resolution Temporal Dynamics Of Gaba and Glxmentioning
confidence: 73%
See 4 more Smart Citations
“…By contrast, we found no relationships between the change in different metabolite concentrations. (Kurcyus et al, 2018). This work revealed that GABA+ concentrations were higher when participants had their eyes closed, compared to open in darkness, while Glx concentration was lower when participants eyes were closed, compared to when receiving visual stimulation.…”
Section: Low Resolution Temporal Dynamics Of Gaba and Glxmentioning
confidence: 73%
“…To compare these with data measured from another brain region, we reanalysed previously gathered MR spectroscopic data targeting the posterior cingulate cortex (Mikkelsen et al, 2017(Mikkelsen et al, , 2019. For the purpose of further comparison, we also reanalysed data from a study investigating metabolite concentrations in the visual cortex under different viewing conditions (Kurcyus et al, 2018).…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations